Evaluating variation in feed attributes of elite grain sorghum cultivars - Agyemang, K.; Larbi, Asamoah; Murty, D.S. (Elsevier, 1998)
Current cereal breeding programmes at commodity-oriented research centres emphasize grain yields with little consideration for fodder yield and quality. In farming systems with livestock, the use of varieties with high-grain yields but low stover yields may be rejected by farmers. This study investigated the variability in chemical characteristics and digestibility of stovers among 10 `best-bet' sorghum cultivars selected for grain yield with the view to study the merits of selecting among cultivars for feed attributes. Cluster analysis of N, ADF and NDF obtained from chemical analyses, and in sacco dry matter digestibility of stovers showed that wide intercultivar variations existed at the three-cluster solution (designated cluster groups III, IV, V). Cultivar BES, the only member of group IV, had a relatively high N content (90 g kg-1 DM), a high 48 h dry matter loss (637 g kg-1 DM) and relatively low ADF and NDF values (386 and 598 g kg -1 DM). Members of group V (KSV 8 and Gaya Early) contained the lowest N (67 g kg-1 DM), lowest digestibility coefficient (511 g kg-1 DM) and highest ADF and NDF values 466 and 665 g kg-1 DM). Values for members of group III (ICSV 111, ICSV 210, ICSV 247, ICSV 400, ICSH 89009NG and ICSH 89002NG) were intermediate. There were no significant correlations between indicators of nutritive values, grain yield and grain mass. The results suggest existence of variation in indicators of nutritive values within the cultivars to warrant consideration for selection among these for detailed nutritional studies, and that improving the nutritive values within the cultivars to warrant consideration for selection among these for detailed nutritional studies, and that improving the nutritive value in stovers through breeding may not necessarily impair grain yield and grain mass.